Preparation of submicron boron carbide powder through gas-solid reaction method. Issue 12 (15th August 2019) - Wei, Hongkang; Li, Chenran; Zhao, Lin; Lang, Ying; Deng, Xiangyu; Wu, Fan; Wang, Chang-an; Xie, Zhipeng
Abstract: Boron carbide submicron powder was synthesized with boron oxide and graphene as starting materials by gas-solid reaction method using two different apparatuses. The effects of calcination temperature and holding time, apparatus type and B2 O3 /C ratio of the starting materials on the phase composition and morphology of the synthesized powders were evaluated. A newly formed residual carbon morphology distinct from original graphene were present in samples synthesized at a higher B2 O3 /C ratio or temperature. The synthesis temperature of ∼1500 °C was found to be more suitable to obtain boron carbide powder without the existence of residual carbon. The new type of apparatus enabled the synthesis of boron carbide phase at a relatively lower temperature, due to its more efficient use of B2 O3 vapor.